Are emotions contagious? A conceptual review of studies in language education - Kong, Yu (Frontiers in Psychology, 2022)
Considering the great role those affective variables play in language learning, it seems wise to hypothesize whether teacher and learner emotions are contagious in the language classroom or not. The existing literature on emotion contagion in other fields of study accepts this hypothesis and reveals significant points about the verbal and nonverbal cues for emotion contagion in class. The present paper introduces and defines the topic and goes on with summarizing the procedure of transmitting the emotion. Then, it reviews the existing research on emotion contagion in different areas and creates a link between them and the L2 studies. It draws attention to the dearth of research on emotion contagion in the second language acquisition (SLA) domain and emphasizes the need for innovative dynamic approaches to research to explore emotion contagion in the ecology of the English as a Foreign Language (EFL) classroom. It also reviews the limited body of research in this regard in the SLA domain and shows how the significant findings can be useful for L2 educators. The findings of these studies show that more relevant studies in the future can be hoped to provide insightful remarks about how different emotions are transmitted between the teacher and students or among students in L2 classes. These studies are supposed to adopt a dynamic approach as well as a longitudinal data collection and analysis procedure. These can have implications for teacher education programs in the English language teaching (ELT) domain.